Empirical Experience of the Prophet as a Source of Knowledge Hadith Perspective - Nur Annisa Istifarin; Ida Rochmawati (JIA (Jurnal Ilmu Agama), 2024)
Empiricism is a branch of Western epistemology that is based on experience and discourages reason. According to empiricism, the source of knowledge is experience or empirical. Reason is not a source of knowledge; instead, reason is tasked with processing knowledge gained from experience. The aim of this research is to find out hadiths about the life of the Prophet which can constitute epistemology as science. This research uses a descriptive method with a literature review. Thus, this research concludes that the application of Islamic epistemology based on the life of the Prophet is proven in the Muslim hadith no. index 2336 about the wrong story of the Prophet to date palm farmers. This hadith is a tribute to the Prophet because of his expertise and ability in the professional field. In other words, the Prophet's hadith shows that the only people who understand agricultural issues better are farmers. Judging from the asbab al-wurud hadith, the Prophet was born and raised on the barren Arabian Peninsula. Therefore, the Prophet only expressed his opinion without having experience in farming dates. From this experience of the Prophet's erroneous opinions, lessons can be made for farmers, as those who understand more about the world of Islamic boarding schools are the kyai and Islamic boarding school administrators.